Catheter‐based closure of residual leaks after percutaneous occlusion of the left atrial appendage. Issue 7 (23rd December 2015) - Hornung, Marius; Gafoor, Sameer; Id, Dani; Vaskelyte, Laura; Hofmann, Ilona; Franke, Jennifer; Sievert, Horst; Bertog, Stefan C.
Abstract : Introduction: The purpose of this study was to evaluate safety and efficacy of catheter‐based occlusion of residual leaks after percutaneous closure of the left atrial appendage (LAA). Methods: All cases of LAA closure at our center were reviewed to identify secondary interventions for residual leaks. Leaks with a width of more than 3 mm by transesophageal echocardiography (TEE) were considered relevant. In a case‐specific approach, depending on the respective morphology of the defect, either an LAA occlusion device or an Amplatzer Vascular Plug was implanted under TEE and fluoroscopic guidance. Results: Between June 2003 and December 2013, 12 patients underwent residual leak closure. All procedures were technically successful and without complications. In 10 cases (83%), complete sealing was confirmed at TEE follow‐up. In 2 patients, minimal gaps (2–3 mm) persisted and anticoagulation was continued. None of the patients had strokes during the follow‐up period. Conclusion: Percutaneous residual leak closure after attempted LAA occlusion can be done safely and with high procedural success rates. © 2015 Wiley Periodicals, Inc.